2012
DOI: 10.4187/respcare.01141
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Use of Noninvasive Ventilation After Extubation: A Prospective, Multicenter Randomized Controlled Trial

Abstract: Preventive use of NIV after extubation in patients who passed spontaneous breathing trial did not show benefits in decreasing extubation failure rate or the mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 20 publications
5
56
0
7
Order By: Relevance
“…65,66 Another RCT 67 in patients with hypercapnia at the time of extubation prospectively confirmed the latter findings, but these results were not confirmed when NIV was applied to all patients after extubation, without selecting the patients at higher risk. 68 Two other earlier RCTs tested the hypothesis that NIV could avoid reintubation in patents already showing signs of acute respiratory distress within the first 48 hours after extubation, but found no reduction in reintubation rate, 69 and one 70 even found significantly higher ICU mortality in the NIV group, associated with longer delay in reintubation. Interestingly enough, a pilot study performed in patients extubated early after hypoxic respiratory failure showed that NIV was very useful as a bridge to unsupported breathing, reducing the frequency of post-extubation failure.…”
Section: Prevention Of Extubation Failurementioning
confidence: 98%
“…65,66 Another RCT 67 in patients with hypercapnia at the time of extubation prospectively confirmed the latter findings, but these results were not confirmed when NIV was applied to all patients after extubation, without selecting the patients at higher risk. 68 Two other earlier RCTs tested the hypothesis that NIV could avoid reintubation in patents already showing signs of acute respiratory distress within the first 48 hours after extubation, but found no reduction in reintubation rate, 69 and one 70 even found significantly higher ICU mortality in the NIV group, associated with longer delay in reintubation. Interestingly enough, a pilot study performed in patients extubated early after hypoxic respiratory failure showed that NIV was very useful as a bridge to unsupported breathing, reducing the frequency of post-extubation failure.…”
Section: Prevention Of Extubation Failurementioning
confidence: 98%
“…7 Investigators have also used NIV in asthma, pneumonia, neuromuscular disease, post-extubation, and hypoxemic and postoperative acute respiratory failure, with varying success. [8][9][10][11][12][13][14][15] The timing and location of initiation of NIV has been evaluated by investigators. Early commencement of NIV in appropriate patients is associated with better outcomes, because delay can adversely affect the patient and increase the need for invasive ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…This selection should include a high risk of post-extubation respiratory failure, a condition likely to respond to low level ventilatory support, and the minimization of factors that impair the effectiveness of NIV (inadequate airway clearance and mental status). The unselective approach of the Su et al study, 14 at least as far as the first 2 elements, seems not beneficial. The criteria for selection in the other studies, [11][12][13] although with few in common, were quite different from each other.…”
mentioning
confidence: 83%
“…ICU and hospital length of stay and mortality were no different, but an intriguing 90 day mortality advantage for the preventive NIV group was noted. SEE THE ORIGINAL STUDY ON PAGE 204 In this issue of RESPIRATORY CARE, Su et al 14 report a large prospective randomized trial performed in 3 ICUs in Taiwan, aiming to evaluate whether the preventive use of NIV after planned extubation would reduce re-intubation rate. Different from prior studies, this study did not select patients according to risk of post-extubation respiratory failure.…”
mentioning
confidence: 99%